2021
DOI: 10.1016/j.str.2020.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-EM structure of CtBP2 confirms tetrameric architecture

Abstract: C-terminal binding proteins 1 and 2 (CtBP1 and CtBP2) are transcriptional regulators that activate or repress many genes involved in cellular development, apoptosis and metastasis. CtBP proteins are activated under hypoxic conditions where NAD(H) levels tend to be higher. NADH-dependent activation of CtBP2 has direct implication in multiple types of cancers and poor patient prognosis. Previous studies have proposed dimeric CtBP as the relevant oligomeric state, however our studies with multi-angle light scatte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 53 publications
(38 reference statements)
0
22
0
Order By: Relevance
“…F H I G significant differences in CT perfusion parameters and MVD measurements of esophageal cancer with different differentiation levels and pathological types, which was consistent with some foreign literature reports. Tumor growth is mainly supported by new blood vessels with nutrients, which is the pathological basis for tumor cell metastasis and invasion, accounting for approximately 1-10% of the tumor volume (16). According to the definition, BF is mainly determined by the characteristics of tumor BF and the density of microvessels inside the tumor, which reflects the BF in the local area.…”
Section: A B C D Ementioning
confidence: 99%
“…F H I G significant differences in CT perfusion parameters and MVD measurements of esophageal cancer with different differentiation levels and pathological types, which was consistent with some foreign literature reports. Tumor growth is mainly supported by new blood vessels with nutrients, which is the pathological basis for tumor cell metastasis and invasion, accounting for approximately 1-10% of the tumor volume (16). According to the definition, BF is mainly determined by the characteristics of tumor BF and the density of microvessels inside the tumor, which reflects the BF in the local area.…”
Section: A B C D Ementioning
confidence: 99%
“…Although oligomerization has most often been considered as dimerization, we ( 41 ) and others ( 34 ) have demonstrated that the primary effect of NAD(H) is to promote assembly of CtBP dimers into tetramers. Moreover, we have recently established the transcriptional relevance of the tetrameric forms by showing that tetramer-destabilizing mutants of CtBP2 are defective for oncogenic activity ( 42 ). Our results here have identified the phosphate groups as central for NAD(H)-linked assembly of tetrameric CtBP and also identified an important difference between CtBP1 and CtBP2 that emanates from a short peptide segment that connects the two subdomains.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of CtBP, substantial evidence exists that oligomerization is linked with NAD(H) binding ( 5 , 29 , 33 , 34 , 35 , 36 ), and dimer-destabilizing mutants inhibit transcriptional function ( 37 , 38 , 39 , 40 ). Although assembly of CtBP has primarily been considered in terms of dimers, there is accumulating evidence that NAD(H) binding triggers the assembly of two CtBP dimers to form tetrameric dimers of dimers ( 33 , 34 , 35 , 41 , 42 ). Moreover, we have recently shown that tetramer-destabilizing mutants of CtBP2 are defective for oncogenic activity ( 42 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The transcriptional co-repressor C-terminal binding protein (CtBP) has been originally named thus, since it binds to the five amino acid domains (PLDLS) at the C-terminus of the adenovirus early region 1A (E1A) protein ( 12 14 ). The CtBP protein, including the CtBP1 and CtBP2 protein isoforms, is an evolutionarily conserved transcriptional repressor that has been reported to specifically bind to DNA or protein targets and function as a bridge molecule between DNA-binding proteins and transcriptional repressors, thereby inhibiting gene transcription ( 15 ). In addition, CtBP has been revealed to promote epithelial-mesenchymal transition (EMT) by inhibiting E-cadherin expression ( 14 , 16 ).…”
Section: Introductionmentioning
confidence: 99%